Analysis of colistin resistance in carbapenem-resistant Enterobacterales and XDR Klebsiella pneumoniae. (February 2022) - Bir, Raunak; Gautam, Hitender; Arif, Nazneen; Chakravarti, Priyanka; Verma, Jyoti; Banerjee, Sayantan; Tyagi, Sonu; Mohapatra, Sarita; Sood, Seema; Dhawan, Benu; Chaudhry, Rama; Kapil, Arti; et al.
Introduction: Increasing occurrence of infections caused by multidrug-resistant Gram-negative bacteria resulted in colistin being the last agent for treatment. Apart from plasmid-mediated mcr genes, mutations involving several genes like mgrB, phoP/phoQ, pmrA, pmrB, pmrC, and crrABC genes, are leading causes of colistin resistance. Four colistin susceptibility testing methods were compared against broth microdilution (BMD) and determined the presence of the mcr1-5 gene. Methodology: A total of 100 carbapenem-resistant Enterobacterales isolates were tested for colistin susceptibility by commercial broth microdilution (cBMD), E-test, VITEK-2, and rapid polymyxin NP assay (RPNP) and compared with BMD. The presence of the mcr1-5 gene was determined by modified RPNP and PCR. Two non- mcr colistin-resistant XDR isolates were subjected to whole-genome sequencing using Illumina MiSeq sequencing platform. Results: Among 100 carbapenem-resistant Enterobacterales isolates, 15% were resistant to colistin. Essential agreement, categorical agreement, major error, and very major error for cBMD/E-test/VITEK-2/RPNP were 96%/73%/82%/NA; 99%/86%/88%/91%, 1.2%/9.4%/11.8%/8.2% and 0%/40%/13.3%/13.3%, respectively. Only one Klebsiella pneumoniae isolate harbored the mcr-1 gene, observed by both methods. Whole-genome sequencing of two non- mcr XDR Klebsiella pneumoniae showed multiple mutations in 10 genes responsible for lipopolysaccharide biosynthesis. Conclusions: The performance of cBMD was excellent, whereas the E-test was unacceptable. VITEK-2 and RPNP performed better but remained unreliable due to high error rates. Multiple mutations in the target proteins involving lipopolysaccharide formation, modification, and regulation were seen, resulting in colistin resistance.